2020
DOI: 10.3390/su12239917
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Supernatants of Plant Growth-Promoting Bacteria: A Review of Their Use as Biostimulant and Microbial Biocontrol Agents in Sustainable Agriculture

Abstract: Plant growth-promoting bacteria (PGPB) afford plants several advantages (i.e., improvement of nutrient acquisition, growth, and development; induction of abiotic and biotic stress tolerance). Numerous PGPB strains have been isolated and studied over the years. However, only a few of them are available on the market, mainly due to the failed bacterial survival within the formulations and after application inside agroecosystems. PGPB strains with these challenging limitations can be used for the formulation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 136 publications
3
40
0
Order By: Relevance
“…Our results revealed that the pre-treatment of grape berries with a culture broth containing both Bvel1 bacterial cells and their secreted metabolites resulted in the colonization of wounded grape berries and a remarkable reduction in the grey mold ingress and growth on wounds 3 or 6 days after artificial inoculation. Our data are in agreement with previous observations, where it was demonstrated that the treatment of fruits and vegetables with cell suspensions, cell cultures, CFCS, or CFCS-extracted metabolites from BCAs significantly reduced the ingress and growth of pre-harvest and post-harvest pathogenic fungi [ 50 , 51 , 52 ]. However, recent studies have demonstrated that effective biocontrol is achieved when the concentration of applied/produced pure elicitors such as plipastatin, iturin, and bacillomycin D on the target tissue is in micromolar amounts (10–50 μM) [ 16 , 44 , 47 , 53 ]; a concentration that is almost equal to their MIC values [ 16 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results revealed that the pre-treatment of grape berries with a culture broth containing both Bvel1 bacterial cells and their secreted metabolites resulted in the colonization of wounded grape berries and a remarkable reduction in the grey mold ingress and growth on wounds 3 or 6 days after artificial inoculation. Our data are in agreement with previous observations, where it was demonstrated that the treatment of fruits and vegetables with cell suspensions, cell cultures, CFCS, or CFCS-extracted metabolites from BCAs significantly reduced the ingress and growth of pre-harvest and post-harvest pathogenic fungi [ 50 , 51 , 52 ]. However, recent studies have demonstrated that effective biocontrol is achieved when the concentration of applied/produced pure elicitors such as plipastatin, iturin, and bacillomycin D on the target tissue is in micromolar amounts (10–50 μM) [ 16 , 44 , 47 , 53 ]; a concentration that is almost equal to their MIC values [ 16 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our data are in agreement with previous observations, where it was demonstrated that the treatment of fruits and vegetables with cell suspensions, cell cultures, CFCS, or CFCS-extracted metabolites from BCAs significantly reduced the ingress and growth of pre-harvest and post-harvest pathogenic fungi [ 50 , 51 , 52 ]. However, recent studies have demonstrated that effective biocontrol is achieved when the concentration of applied/produced pure elicitors such as plipastatin, iturin, and bacillomycin D on the target tissue is in micromolar amounts (10–50 μM) [ 16 , 44 , 47 , 53 ]; a concentration that is almost equal to their MIC values [ 16 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although the disease-suppressing effect of biological control agents is weaker than that of chemical fungicides, the application of KOF112 having antagonistic activities toward a wide range of phytopathogenic fungi, including Ascomycetes and Oomycetes , may contribute to reducing the frequency of chemical fungicide application in viticulture, as well as to inhibiting the development of chemical fungicide resistance. The supernatants of biological control agents could be used as a new biostimulant in sustainable agriculture [ 26 ]. The supernatant of B. subtilis GLB191, which contains surfactin and fengycin, exerted a direct antifungal effect and induced plant defense response, thereby contributing to protection against grape downy mildew [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diffusible and volatile compounds produced by Streptomyces also act against the polymeric compounds of fungal pathogens, such as chitin [44]. Cell-free supernatants produced by Streptomyces are a valid source of biocontrol metabolites against F. oxysporum and R. solani [45][46][47][48][49]. Recent work by Lyu and collaborators demonstrated that reveromycin A and B-polyketides compounds with strong antifungal activity-extracted from Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%